PENGEMBANGAN E-MODUL FISIKA BERBASIS PENDEKATAN SAINTIFIK PADA MATERI TEORI KINETIK GAS - Putri, Irna Tri; Aminoto, Tugiyo; Pujaningsih, Febri Berthalita (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2020)
This research is motivated by the difficulties experienced by students in understanding gas kinetic theory material and the limitations of multimedia teaching materials possessed by teachers. The purpose of this study is to develop a physics-based e-module based on the Scientific Approach using 3D Professional Pageflipp on the gas kinetic theory material and to determine students' perceptions of the e-modules developed. This type of research is research and development using the ADDIE development model (Analyze, Design, Development, Implementation and Evaluation). This research only reached the Development stage. The resulting e-module serves as a source of student independent learning and teaching materials that can be used by students in the classroom in the learning process based on the Scientific Approach. The results of this study are e-module that were developed through a validation process by a team of experts and were declared eligible to be tested on students. From the results of testing the students' perception data it was concluded that this e-module is good for use in the learning process.